2012
DOI: 10.5601/jelem.2012.17.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilization on the yield and nutritive value of Beta vulgaris L.

Abstract: Leaf beet is one of several types of Beta vulgaris L. The vegetable originates from the Mediterranean area but is currently grown on a large scale in the US and Western Europe, e.g. Switzerland, Germany, France or England. In Poland, it is a less known vegetable, despite its high content of many valuable nutrients and excellent taste. One of the main factors affecting the size and quality of yield is nitrogen fertilization. Nitrogen is a structural element of plants and its deficiency significantly inhibits pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Nitrogen is an essential macronutrient that promotes plant development and crop yield and quality [27][28][29][30]. Many studies have claimed that N is an essential element involved in the biosynthesis of chlorophyll [31], nucleic acids [32], amino acids [33], and enzymes [34], which are associated with the accumulation of plant nutrients [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is an essential macronutrient that promotes plant development and crop yield and quality [27][28][29][30]. Many studies have claimed that N is an essential element involved in the biosynthesis of chlorophyll [31], nucleic acids [32], amino acids [33], and enzymes [34], which are associated with the accumulation of plant nutrients [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Estas diferencias se pueden explicar por el aporte de N y K al suelo generado por U. europaeus (Tabla 2). Dzida et al (2012) Por otra parte, cuando el vegetal absorbe exceso de nitratos, el valor nutritivo de la planta es menor (Dzida et al, 2012). Según Miceli y Miceli (2014) dosis de N superiores a 200 kg ha -1 se traducen en acumulación de nitratos en B. vulgaris L. var.…”
Section: Resultados Y Discusiónunclassified
“…Al respecto, Dzida et al (2012) afirman que el principal factor que afecta al tamaño, calidad y rendimiento es la fertilización nitrogenada.…”
Section: Introductionunclassified
“…There are varied observations from literature regarding the effect of N on the accumulation of vitamin C in plants. Some researchers have reported that increasing doses of nitrogen depressed vitamin C content (Dzida, Jarosz & Michalojc, 2012;Rajasree & Pillai, 2012;Stefanelli, Goodwin & Jones, 2010;Welch, 2016). Contrary, Miceli & Miceli (2014); Hassan, Mijin, Yuseff, Ding &Wahab (2012) andIvanovic.…”
Section: Vitamin Cmentioning
confidence: 99%